Klinische Sportmedizin - Kornbeck J (Dynamic Media Sales Verlag, 2015)
The fight against dopingdepends largely on private regulation but needs public trust to be sustainable in the long term. The paper discusses the implications of this realisation to make the case that increased transparency could strengthen the fight against doping. Because the World Anti-Doping Code (WADC) is a legally non-binding text from a non-governmental organisation (NGO), the standard of proof, known from criminal courts, and the usual evidence requirements applicable in parliamentary legislative procedures are not mandatory. In this situation, increasing transparency could help tackle the epistemological challenges of the fight against doping, which is currently very complex, to protect the rights of accused athletes and ultimately to restore public trust. Drawing on recent policy debatesand recent case law, the paper argues that a voluntary departure from some of the current principles of anti-doping governance could make anti-doping more sustainable in the long term. The system (not athletes) should demonstrate that it has the ability to handle cases fairly. The increasing involvement of public authorities in anti-doping and the quasi-penal nature of the sanctions system make it natural to move closer to the normative framework of the public sector.KEY WORDS:Anti-Doping Fight, anti-Doping Policy, Evidence-Based Policy, Evidence of Doping, Presumption of Innocence